Affecting Factor for Muslim Women to Achieve their Political Rights in Muslim Majority Country - Diastama Anggita Ramadhan (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2020)
Abstract The aim of this article is to observe the different between two Muslim majority countries in relation to how they treat their women to achieve their political rights. The article will find the common ground between Indonesia in terms of women political rights. Later on the discussion, this article explains the main reason why both Muslim countries could have a different way to treat their women citizen. The women political rights in Muslim majority country have been an issue for a long time. This condition has become paradox for the Islamic society itself since the Holy Quran explains that every man and women are equal. In Saudi Arabia, unfortunately, the opportunity for women to access their political rights is exacerbated by the patriarchy condition among the Muslim people that believe that the Man should always be a leader. The application of the Convention on the Elimination of all Forms of Discrimination against Women (CEDAW) seems not having any power at all to fight the inequality. However, the condition in Indonesia was very distinct for Indonesian Muslim women. Indonesia has elected the first Muslim women as a President in 2002. Since the Democratic regime entered the country, the opportunity for woman to access their political rights become much higher.